Stress and the Suppression of Subordinate Reproduction in Cooperatively Breeding Meerkats - Young, Andrew J.; Carlson, Anne A.; Monfort, Steven L.; Russell, Andrew F.; Bennett, Nigel C.; Clutton-Brock, Tim (Proceedings of the National Academy of Sciences - PNAS, 2006)
In many animal societies, dominant individuals monopolize reproduction, but the tactics they employ to achieve this are poorly understood. One possibility is that aggressive dominants render their subordinates infertile by inducing chronic physiological "stress." However, this hypothesis has been discarded largely for cooperatively breeding species, where reproductive monopolies are often extreme. Here we provide strong support for the stressrelated suppression hypothesis in a cooperative mammal, the meerkat (Suricata suricatta). When pregnant, dominant females subject some subordinate females to escalating aggression, culminating in temporary evictions from the group. While evicted, subordinate females suffer chronic elevation of their glucocorticoid adrenal hormone levels, reproductive down-regulation (reduced pituitary sensitivity to gonadotropin-releasing hormone), reduced conception rates, and increased abortion rates. Rather than constantly harassing all subordinate females, dominants only become aggressive when pregnant themselves (when subordinate reproduction would otherwise conflict with their own) and target those females with whom reproductive conflict is most likely (older, pregnant, and more distantly related females). Our findings suggest that dominant female meerkats employ stressful evictions to suppress reproduction among their probable competitors, when attempting to breed themselves. Given the lack of evidence for stress-related suppression in other cooperative breeders to date, it is clear that social stress alone cannot account for the reproductive failure of subordinates across such societies. However, our findings raise the possibility that, in some cooperative breeders at least, dominants may employ stress-related suppression as a backup mechanism to guard against lapses in reproductive restraint by their subordinates.